2008
DOI: 10.1007/s10548-007-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

First Valence, Then Arousal: The Temporal Dynamics of Brain Electric Activity Evoked by Emotional Stimuli

Abstract: The temporal dynamics of the neural activity that implements the dimensions valence and arousal during processing of emotional stimuli were studied in two multi-channel ERP experiments that used visually presented emotional words (experiment 1) and emotional pictures (experiment 2) as stimulus material. Thirty-two healthy subjects participated (mean age 26.8 +/- 6.4 years, 24 women). The stimuli in both experiments were selected on the basis of verbal reports in such a way that we were able to map the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 37 publications
10
64
2
4
Order By: Relevance
“…It is also supported by imaging studies, which suggest distinct neural systems for the processing of valence and arousal (Anders et al, 2004;Lewis et al, 2007;Kensinger and Corkin, 2004). Recently, similar distinctions were also reported for EEG data (Gianotti et al, 2008), where a microstate analysis revealed different dynamics and neural assemblies for the processing of valence and arousal.…”
Section: Introductionsupporting
confidence: 54%
“…It is also supported by imaging studies, which suggest distinct neural systems for the processing of valence and arousal (Anders et al, 2004;Lewis et al, 2007;Kensinger and Corkin, 2004). Recently, similar distinctions were also reported for EEG data (Gianotti et al, 2008), where a microstate analysis revealed different dynamics and neural assemblies for the processing of valence and arousal.…”
Section: Introductionsupporting
confidence: 54%
“…An advantage of topographic ERP analysis over traditional waveform analysis is that it enables to bypass the issue of reference-dependent classic ERP analysis and the issue regarding a priori selection of electrodes or time period (see: [53]). This method has been used several times, with faces [31, 35, 60] or emotion [61, 62]. …”
Section: Methods and Methodsmentioning
confidence: 99%
“…The interaction requires the completion of initial modulations of arousal and valence (Delplanque et al, 2006;Dolcos and Cabeza, 2002;Gianotti et al, 2008). Thus, it is expected that it emerges late.…”
Section: Arousal Processing Is Prioritized Followed By Valence and Lamentioning
confidence: 99%